Athaliah and Alexandra: Gender and Queenship in Josephus - Scales, Joseph (Journal of ancient Judaism, 2020)
Athaliah and Alexandra were the only two women to rule as queens of Judah/Judaea in their own right and both women’s reigns are reported in Josephus’ writings. Despite their uniqueness, however, Athaliah and Alexandra are rarely compared in scholarship; the former is usually dismissed, and focus centred on the latter. This article contends that there are historical similarities between the two, but literary differences. Josephus could have referred to Athaliah or used elements of her portrayal in his presentation of Alexandra but does not, creating the impression that Alexandra was completely different to her predecessor. It may be instructive, therefore, to consider why Josephus literarily isolates the queens and what this means for his interpretation of Alexandra.